UNDERSTANDING DIFFERENT ENGLISH ACCENTS (Modern education and development, 2025)
English sounds different depending on where it is spoken. Whether it is a British accent, an American twang, or an Aussie drawl, each English accent offers a unique way of communicating. For learners, understanding these accents is essential - not just for language proficiency, but for building stronger connections with people from different backgrounds. Accents are more than just variations in speech, they reflect cultural identities and help shape how we communicate with others. This article explores why understanding different English accents is so important for language learners.